Poverty, women’s empowerment and social entrepreneurship among b40 urban women in Malaysia - Faten Nadhirah Muhammad Fauzi, Rohaiza Rokis, Norasikin Basir Sharifah Fatimah AlZahrah Syed Hussein, (Opción, 2019)
The current study investigates the level of awareness and intention on social entrepreneurship among B40 women in urban areas. Data are obtained through set structured interview items and analyzed with the assistance of Atlasti 8. The initial main finding indicates that B40 urban women have no indicative understanding of social entrepreneurship even after layman terms and contexts are applied. In conclusion, as long as B40 urban women believe that they are generating a positive return to society, social entrepreneurship is possible. It is noted that social entrepreneurship can be in major community development projects as well as health care.